Do Obsessions and Compulsions Exist Among Outpatients with Social Anxiety Disorder? - Tómas Páll Þorvaldsson 1985- (2015)
Recurrent intrusive images exist across mental disorders. However, the specific content of intrusive images varies depending on disorders. Theoretical models of how intrusive images develop into clinical obsessions are primarily cognitive-behavioral therapy (CBT) models on how obsessive-compulsive disorder (OCD) develops. In this study, it was hypothesized that individuals with social anxiety disorder (SAD) were likely to react to intrusive images with compulsive behaviors (including neutralizations). Participants were 32 outpatients (M age = 29; SD = 11.8; 53.1% female) at an anxiety treatment center in Iceland diagnosed with SAD (according to the Mini International Neuropsychiatric Interview; MINI). Participants were interviewed with a semi-structured interview to assess imagery in SAD, which was adapted to focus specifically on reactions to intrusive images. Sixty-two percent of the participants reported experiencing intrusive images with 90% of those patients reporting at least one compulsive and/or neutralizing strategy in response to the intrusive image. This initial study is a first step toward establishing that obsessions and compulsions may exist in SAD as a maintaining process. There appear to be greater similarities between SAD and obsessive-compulsive spectrum disorders such as OCD and BDD than previously believed. Future directions and treatment implications are discussed. Keywords: Obsessions, compulsions, neutralization, social anxiety disorder.